Antioxidant Maja Fruit (Aegle marmelos (L) Carrea) Lowering Blood Sugar Mus Musculus - Sukian Wilujeng; Pramita Laksitarahmi I.; Suharnanik Suharnanik; Printa Tiaranisa (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Maja fruit crops (Aegle Marmelos (L) Correa) is very popular with the culture of the Majapahit kingdom, the kingdom is the biggest in Indonesia in the 13th century. Maja fruit tastes bitter with light green skin. Because of the bitter taste of this fruit then nothing like it, but provide tremendous benefit in lowering blood sugar. This study found that the method of testing the antioxidant activity of maja fruit extract samples was very strong with values reaching the IC50 range of 50-100 µg/mL. Trials of mice were also carried out and proven to reduce sugar levels. Also interesting from the results of this study produce maja fruit in the form of a drink that no longer tastes bitter but changes the taste to be rather sweet, warmer when drinking it as there are natural alcohol levels that are quite safe for the body.